Changing management of HIV in pregnancy: service development following the introduction of universal antenatal screening. (7th June 2011) - Shillito, J; Sparey, C; Katsafourou, P; Perry, A
Abstract : Universal antenatal screening for HIV was introduced in 2000 with the aim of screening 90% of the population and offering interventions to those infected; aiming to reduce the incidence of mother to child transmission by 80%. Our multidisciplinary team cares for one of the largest populations of HIV positive pregnant women in the UK. The current prevalence in our antenatal population is 1 in 143. Over the last decade, there has been a rise in patient numbers, a change in racial mix and significant changes in practice in response to emerging evidence. Our uptake of screening is over 99% with a mother to child transmission rate of 0.4%. Of the two infected babies, one was born to a mother who refused treatment and one was thought to have been infected through breastfeeding. Since the BHIVA guidelines in 2005 we have been offering vaginal delivery to women with an undetectable viraemia at 36 weeks. Currently over 54% of women deliver vaginally but with a 33% emergency caesarean section rate. It is not yet clear whether this emergency delivery might increase perinatal transmission. The next area for potential change is the introduction of exclusive breastfeeding.